A tale of a snakebite victim from vicinity of bite through the health system of Bangladesh - Fairouz, Fariha; Ahsan, HM Nazmul; Amin, Md Robed; Faiz, Mohammad Abul (Bangladesh Journal of Medicine, 2021)
Abstract not available Bangladesh J Medicine July 2021; 32(2) : 161-164